Complex contention: analyzing power dynamics within Anonymous. (4th July 2017) - Uitermark, Justus
Abstract: Anonymous is notoriously elusive as the movement takes on radically different guises, constantly mutates, and traverses national borders and ideological divides. Since Anonymous is difficult to grasp with conventional social movement theory, this paper uses insights from complexity theory to analyze the movement's evolution in general and its dynamics of power in particular. While participants in Anonymous radically reject hierarchy and leadership, dominant groups emerged at various points in the movement's evolution. This paper aims to explain how such dominant groups emerge and concentrate power and how they subsequently dissolve and lose power. Drawing on ethnographic research as well as secondary sources, it identifies mechanisms of power concentration and diffusion within nominally horizontalist movements.